Effects of the NKCC1 inhibitors bumetanide, azosemide, and torasemide alone or in combination with phenobarbital on seizure threshold in epileptic and nonepileptic mice. (1st March 2021) - Hampel, Philip; Römermann, Kerstin; Gailus, Björn; Johne, Marie; Gericke, Birthe; Kaczmarek, Edith; Löscher, Wolfgang
Abstract: The sodium-potassium-chloride (Na–K–Cl) cotransporter NKCC1 is found in the plasma membrane of a wide variety of cell types, including neurons, glia and endothelial cells in the brain. Increased expression of neuronal NKCC1 has been implicated in several brain disorders, including neonatal seizures and epilepsy. The loop diuretic and NKCC inhibitor bumetanide has been evaluated as an antiseizure agent alone or together with approved antiseizure drugs such as phenobarbital (PB) in pre-clinical and clinical studies with varying results. The equivocal efficacy of bumetanide may be a result of its poor brain penetration. We recently reported that the loop diuretic azosemide is more potent to inhibit NKCC1 than bumetanide. In contrast to bumetanide, azosemide is not acidic, which should favor its brain penetration. Thus, azosemide may be a promising alternative to bumetanide for treatment of brain disorders such as epilepsy. In the present study, we determined the effect of azosemide and bumetanide on seizure threshold in adult epileptic mice. A structurally related non-acidic loop diuretic, torasemide, which also blocks NKCC1, was included in the experiments. The drug effects were assessed by determing the maximal electroshock seizure threshold (MEST) in epileptic vs. nonepileptic mice. Epilepsy was induced by pilocarpine, which was shown to produce long-lasting increases in NKCC1 in the hippocampus, whereas MEST did not alter NKCC1 mRNA in this region. None of the three loop diuretics increased MEST or the effect of PB on MEST in nonepileptic mice. In epileptic mice, all three diuretics significantly increased PB's seizure threshold increasing efficacy, but the effect was variable upon repeated MEST determinations and not correlated with the drugs' diuretic potency. These data may indicate that inhibition of NKCC1 by loop diuretics is not an effective means of increasing seizure threshold in adult epilepsy. Highlights: Alterations in the chloride cotransporter NKCC1 have been implicated in epilepsy. The antiseizure efficacy of the NKCC1 inhibitor bumetanide is restricted by its poor brain penetration. Here we examined whether the NKCC1 inhibitors azosemide or torasemide are more effective. Drug effects on seizure threshold or the activity of phenobarbital were determined. All 3 diuretics increased phenobarbital's effect in epileptic mice but the effect was variable.